Cellular dynamics of neuronal migration in the hippocampus - Hayashi, Kanehiro; Kubo, Ken-ichiro; Kitazawa, Ayako; Nakajima, Kazunori (Frontiers in Neuroscience, 2015)
A fine structure of the hippocampus is required for proper functions, and disruption of this formation by neuronal migration defects during development may play a role in some psychiatric illnesses. During hippocampal development in rodents, pyramidal neurons in the Ammon’s horn are mostly generated in the ventricular zone, spent as multipolar cells just above the ventricular zone, and then migrate radially towards the pial surface, ultimately settling into the hippocampal plate. Although this process is similar to that of neocortical projection neurons, these are not identical. In addition to numerous histological studies, the development of novel techniques gives a clear picture of the cellular dynamics of hippocampal neurons, as well as neocortical neurons. In this article, we provide an overview of the cellular mechanisms of rodent hippocampal neuronal migration including those of dentate granule cells, especially focusing on the differences of migration modes between hippocampal neurons and neocortical neurons. The unique migration mode of hippocampal pyramidal neurons might enable clonally related cells in the Ammon’s horn to distribute in a horizontal fashion.